Downstaging Conversion Therapy in Patients With Initially Unresectable Advanced Hepatocellular Carcinoma: An Overview - Sun, Hui-Chuan; Zhu, Xiao-Dong (Frontiers in Oncology, 2021)
The high mortality rate associated with hepatocellular carcinoma (HCC) is partly due to the high proportion of patients who present with advanced stage disease at diagnosis, for whom there are limited treatment options. For selected patients with initially unresectable HCC, locoregional and/or systemic treatments can result in tumor downstaging and consequently provide opportunities for surgical intervention and the potential for long-term survival. Therefore, the key aim of ‘conversion therapy’ is to reduce tumor burden so that patients become amenable to surgical resection. Various therapies have been investigated as candidates for downstaging patients with potentially resectable HCC including transarterial chemoembolization, transarterial radioembolization with yttrium-90 microspheres, radiotherapy, systemic therapies and combination or multimodality treatment approaches. However, downstaging conversion therapy remains controversial and there are several challenges such as defining the criteria used to identify the population of patients who are ‘potentially resectable’, the criteria used to define successful downstaging, and the optimum treatment approach to maximize the success of downstaging therapy. In this review article, we summarize clinical experience and evidence of downstaging conversion treatment in patients identified as having ‘potentially resectable’ HCC.